2019
DOI: 10.1038/s41598-018-36593-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrochemical Kinetic Properties of 0.5Li2MnO3∙0.5LiCoO2 Cathode Materials with Different Li2MnO3 Domain Sizes

Abstract: Lithium rich layered oxide xLi2MnO3∙(1−x)LiMO2 (M = Mn, Co, Ni, etc.) materials are promising cathode materials for next generation lithium ion batteries. However, the understanding of their electrochemical kinetic behaviors is limited. In this work, the phase separation behaviors and electrochemical kinetics of 0.5Li2MnO3∙0.5LiCoO2 materials with various Li2MnO3 domain sizes were studied. Despite having similar morphological, crystal and local atomic structures, materials with various Li2MnO3 domain sizes exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 60 publications
1
20
1
Order By: Relevance
“…Controlled structural/chemical changes induced by the Li‐TM inter‐diffusion between the two phases in the Li‐rich materials can help to fully exploit oxygen redox reaction in addition to TM redox reaction, resulting in very high energy density. Given the Li‐rich layered materials that are composed of the two layered phases, [ 3b,10a,14b,21 ] the Li‐TM inter‐diffusion between both phases can lead to different composite structure such as the excess Li and Ni incorporation in both layered phases that can remarkably improve reversible oxygen redox activity and layered structure stability. The excess Li in the both layered phases can increase local Li‐rich environments such as Li–O–Li structures leading to the formation of available additional electronic states nearby the oxygen orbital that can activate and increase the oxygen redox reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Controlled structural/chemical changes induced by the Li‐TM inter‐diffusion between the two phases in the Li‐rich materials can help to fully exploit oxygen redox reaction in addition to TM redox reaction, resulting in very high energy density. Given the Li‐rich layered materials that are composed of the two layered phases, [ 3b,10a,14b,21 ] the Li‐TM inter‐diffusion between both phases can lead to different composite structure such as the excess Li and Ni incorporation in both layered phases that can remarkably improve reversible oxygen redox activity and layered structure stability. The excess Li in the both layered phases can increase local Li‐rich environments such as Li–O–Li structures leading to the formation of available additional electronic states nearby the oxygen orbital that can activate and increase the oxygen redox reaction.…”
Section: Resultsmentioning
confidence: 99%
“…[64] Previous studies showed that lithium extraction in Li 2 MnO 3 with a large domain size is more difficult than in a small domain, and more Li 2 MnO 3 components are activated in the latter during cycling. [7,65] However, the irreversible phase transition from Li 2 MnO 3 to LiMn 2 O 4 and the induced defects hinder lithium diffusion. As a result, the lithium ion mobility of an Li 2 MnO 3 sample with large domain size delivered a superior rate performance than the small domain during prolonged cycles.…”
Section: Poor Rate Performance and Impact On Fast Chargingmentioning
confidence: 99%
“…When the GITT technique is used, the cell is charged with a constant current of 5.6 mA/g (C/50 rate) for 1 h and then relaxed for 2 h to reach a near-equilibrium state; this process is then repeated until the final cut-off voltage is reached. During the 1st charge, both samples showed increased polarization in the voltage range >4.5 V or >125 mAh/g, where the oxygen redox reaction is mainly attributed (Figure f). ,, However, the polarization above 4.5 V during the 1st charge is much lower in the CD sample than in the LCD sample (upper, Figure f); this difference indicates that a facile oxygen redox reaction in the CD sample occurs even after almost full extraction of Li. Similarly, the polarization <3.5 V or >125 mAh/g during the 1st discharge process, in which a charge compensation mainly occurs in the oxygen redox reaction, ,, is much lower in the CD sample than in the LCD sample (lower, Figure f).…”
Section: Resultsmentioning
confidence: 97%
“…However, in the 2nd cycle, the contribution of the oxygen redox reaction is much lower than that in the 1st cycle; this change indicates a decrease in the oxygen redox activity. The oxygen redox reaction in 3d-TM-based Li-rich layered materials occurs mainly in the M phase, which has excess Li; therefore, the low oxygen redox activity during the 2nd cycle in the LCD sample may be a result of the irreversible structural change during the 1st cycle.…”
Section: Resultsmentioning
confidence: 99%